Exploring staircases as architectural cues in virtual vertical navigation. Issue 138 (June 2020) - Memikoğlu, İpek and Demirkan, Halime
Highlights: Local architectural cues are seen as salient landmarks. Staircases enable vertical circulation in multi-level buildings. Staircase attributes influence virtual vertical navigation behavior. Virtual navigation and individual differences affect staircase preferences. Interior design heuristics are provided for staircases. Abstract: Architectural design requires experiencing the spatial organization of a building, discovering architectural cues and maintaining spatial orientation during navigation. Architects configure architectural cues in the initial phase of the design process. Staircases, as a feature of local architectural cues that provide access to the other floors in a multi-level building, can have an impact on vertical navigation and aid individuals during navigation and influence their spatial orientation. This study focuses on the issue of vertical navigation during virtual navigation by integrating the individual differences and the geometric attributes of a staircase pair within two different multi-level desktop virtual environments (VEs). The angle between the cue pairs with respect to the same observation point is altered in order to determine the staircase pair that is more efficient in navigation. Virtual vertical navigation is based on an egocentric frame of reference where the participants have control of their movements. Circulation paths, gender differences, navigational abilities and cue pairs are the factors that affect staircase preferences for ascending and descending. For the VE with a 180° difference between the cue pairs, a relationship was found between the ascending and descending staircases. Further analysis indicated that the staircase preference in ascending was either related to the first or last visited rooms on the ground floor. For the VE with a 90° difference between the cue pairs, no relationship was found between the ascending and descending staircases as well as with any other factor. There was only a significant relationship between gender and staircase preference in descending staircases with 180° difference between the cue pairs in favor of females. In addition, there was no significant relationship between the navigational abilities and staircase preferences.